How functional and emotional ads drive smartwatch adoption: The moderating role of consumer innovativeness and extraversion. Issue 3 (3rd June 2019) - Krey, Nina; Chuah, Stephanie Hui-Wen; Ramayah, T.; Rauschnabel, Philipp A.
Abstract : Purpose: The purpose of this paper is to examine advertising strategies' (functional vs emotional) influence on consumers' evaluation and adoption of smartwatches by drawing on the elaboration likelihood model and the schema incongruity theory. Moderating effects of consumer characteristics (personal innovativeness and extraversion) on the value assessment and attitude relationship are also tested. Design/methodology/approach: The model was assessed using partial least squares-structural equation modeling with a sample of 999 non-smartwatch users. Findings: Results show that functional ads elicit higher levels of hedonic than functional (usefulness) and ergonomic values (ease of use), whereas emotional ads produce higher levels of functional (usefulness) in comparison to hedonic value (enjoyment). Collectively, functional, ergonomic, hedonic and symbolic values shape consumers' attitude and their subsequent behavior. In addition, findings demonstrate that extraversion positively moderates the symbolic value–attitude relationship, whereas personal innovativeness negatively moderates the functional value–attitude relationship. Originality/value: Smartwatch sales have floundered despite substantial investments in ad campaigns. This study provides novel insights into managing non-users' value perceptions of smartwatches with the optimal use of ad strategies. Furthermore, it is also one of the first studies to validate the moderating role of extraversion on the symbolic value–attitude link, thus contributing to the emerging literature on wearable technology.